Advances in research on cowpea Striga and Alectra - Singh, B.B.; Emechebe, A.M. (1997)
The parasitic weeds, Alectra vogelii Benth., and Striga gesnerioides (Wild.) Vatke, have become major yield-reducing factors in cowpea. Currently, Striga is more prevalent in the Sudan savanna and Sahelian regions and Alectra in the northern Guinea savanna and southern Sudan savanna regions of West Africa, as well as in East and southern Africa. However, both are fast spreading beyond these limits. Therefore, concerted efforts are being made to develop cowpea varieties resistant to Striga and Alectra, as well as other control measures to minimize yield losses. Systematic research on Striga started in Burkina Faso and on Alectra in Botswana in the early 1980s, which subsequently evolved into a collaborative research effort involving IITA, the Semi-Arid Food Grain Research and Development (SAFGRAD) project, the Natural Resources Institute (NRI). Long Ashton Station (UK), and various national programs. This has led to the identification of several sources of resistance to Striga and Alectra and the development of resistant varieties, as well as systematic studies on strain variation and integrated control. Progress is reviewed.